2009
DOI: 10.1002/tre.121
|View full text |Cite
|
Sign up to set email alerts
|

Adnexal torsion in a postmenopausal woman on tamoxifen

Abstract: The authors describe the case of a postmenopausal woman who presented with sudden-onset abdominal pain and vomiting, found to be caused by a torted haemorrhagic ovarian cyst. The case highlights the occurrence of ovarian cyst formation and endometrial stimulation in patients treated with tamoxifen.A 56-year-old woman presented to the accident and emergency department with sudden onset of left iliac fossa pain and vomiting. The pain was constant and non-radiating. She had associated vomiting of recently eaten f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Cohen et al [ 3 ] in their study reported that diagnosis to surgery timing was significantly longer (24 hours vs. 6 hours) in postmenopausal women when compared with premenopausal women. Various other studies have also reported a delay of 6 hours–6 months from initial presentation to definite management in this age group [ 3 5 6 7 8 9 11 13 ]. Ultrasound with doppler studies of ovarian vessels is usually first investigation ordered to support the diagnosis.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Cohen et al [ 3 ] in their study reported that diagnosis to surgery timing was significantly longer (24 hours vs. 6 hours) in postmenopausal women when compared with premenopausal women. Various other studies have also reported a delay of 6 hours–6 months from initial presentation to definite management in this age group [ 3 5 6 7 8 9 11 13 ]. Ultrasound with doppler studies of ovarian vessels is usually first investigation ordered to support the diagnosis.…”
Section: Discussionmentioning
confidence: 67%
“…In the study by Cohen et al [ 3 ] continuous dull aching pain was the most common symptom present in postmenopausal women whereas premenopausal women mostly presented with acute abdominal pain. Left iliac fossa pain, right inguinal pain with phlank pain, persistent backpain radiating to right groin are also mentioned as presenting complaints in this age group in some of the previous studies [ 6 7 8 ]. Ovarian torsion compromises the blood supply to the ovaries leading to ovarian necrosis and hence can affect fertility in young women of childbearing age, needing aggressive management in terms of laparoscopy or laparotomy with de-torsion of the affected ovary.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations